Exploring the Driving Factors behind Mobile Payment Adoption from the MSMEs’ Perspective - Rahma Ulfa Maghfiroh; Moh. Ilham (UNISSULA, 2025)
This study aims to explore the factors driving mobile payment adoption from the perspective of Micro, Small, and Medium Enterprises (MSMEs). With the advancement of digital technology, mobile payments have become a crucial innovation, expected to enhance the operational efficiency and competitiveness of MSMEs. This research employs a quantitative survey administered to MSMEs in Surabaya. The study measures the influence of performance expectancy, effort expectancy, social influence, trust, and facilitating conditions on behavioral intention and mobile payment adoption. Cluster sampling was used, covering 31 districts in Surabaya, yielding a total of 269 MSMEs. The results show that performance expectancy has a significant positive effect on behavioral intention, effort expectancy does not affect behavioral intention, social influence has a significant positive effect on behavioral intention, trust has a significant positive effect on behavioral intention, facilitating conditions have a significant positive effect on mobile payment adoption, and behavioral intention has a significant positive effect on mobile payment adoption. This research provides valuable insights for stakeholders, particularly in designing more effective strategies to increase mobile payment adoption among MSMEs.